Method for manufacturing retardation film
By stretching a resin film containing a crystalline polymer and then treating it with an organic solvent under tension, the method addresses the challenges of achieving uniform in-plane retardation and thinness in retardation films.
Patent Information
- Application Number
- JP2021543020
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-30
- Filing Date
- 2020-08-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-08-27
AI Technical Summary
Existing methods for manufacturing retardation films with desired retardation and thinness face challenges such as increased variations in thickness and optical properties, and breakage due to high stretching ratios.
A method involving the use of a resin containing a crystalline polymer, where the film is subjected to stretching and then treated with an organic solvent while under tension, to achieve uniform in-plane retardation and adjustable thickness.
This method enables the production of retardation films with excellent uniformity in in-plane retardation and adjustable thickness, overcoming the limitations of previous techniques.
Smart Images

Figure 0007647558000002 
Figure 0007647558000003 
Figure 0007647558000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a retardation film and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art Conventionally, techniques for producing films using resins have been proposed (Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-026909 A [Patent Document 2] Patent No. 6406479 [Patent Document 3] Japanese Patent Application Publication No. 02-064141 Summary of the Invention [Problem to be solved by the invention]
[0004] One type of film manufactured using a resin is a retardation film, which has retardation in at least one of the in-plane direction and the thickness direction, and therefore generally has birefringence in at least one of the in-plane direction and the thickness direction.
[0005] Such a retardation film can be manufactured, for example, by applying stretching treatment to a resin film. When applying stretching treatment to a resin film, the polymer molecules contained in the resin film are generally oriented in the stretching direction. Therefore, by orienting the polymer molecules in the film by stretching treatment, birefringence appears in the film, so that a retardation film having a desired retardation can be obtained.
[0006] In recent years, the thickness of the retardation film is required to be thin. In order to obtain a retardation film that is thin and has a desired retardation, the birefringence of the film can be increased. However, if the stretching ratio is increased in the stretching process in order to obtain a large birefringence, the variation in thickness and optical properties increases, and breakage due to stretching easily occurs, which may make it difficult to stably manufacture the retardation film.
[0007] Under the circumstances described above, the development of a new technology is required as a method for producing a retardation film. The applicant has conducted research and found that a film of a resin containing a polymer having crystallinity exhibits large birefringence when the film is subjected to a heat treatment after a stretching treatment. Based on this finding, the applicant has attempted to produce a retardation film by combining a stretching treatment and a heat treatment.
[0008] Specifically, in the above method, the birefringence is developed by stretching, and then the birefringence is further increased by heat treatment, which can widen the range of birefringence that can be developed in the film, and therefore the thickness can be adjusted with a high degree of freedom while maintaining the magnitude of retardation, and thus it is expected to realize a thin retardation film having a desired retardation.
[0009] However, the above-mentioned method combining the stretching treatment and the heat treatment tends to result in large variations in the in-plane retardation Re of the obtained retardation film. The present invention has been devised in view of the above problems, and aims to provide a retardation film having excellent in-plane retardation uniformity; and a manufacturing method for easily manufacturing a retardation film having excellent in-plane retardation uniformity. [Means for solving the problem]
[0010] The present inventors have conducted extensive research to solve the above problems. As a result, the present inventors have found that when a stretched film made of a resin containing a crystalline polymer is contacted with an organic solvent while applying tension, the optical properties of the stretched film can be adjusted with high uniformity, and as a result, a retardation film having excellent uniformity in in-plane retardation can be obtained. Based on this finding, the present invention has been completed. That is, the present invention includes the following.
[0011] [1] The insulating film is formed of a resin containing a polymer having crystallinity, A retardation film having a coefficient of variation CV(Re) of in-plane retardation at a measurement wavelength of 590 nm of 1.0% or less. [2] The retardation film according to [1], wherein the retardation film contains an organic solvent. [3] The retardation film according to [1] or [2], wherein the crystalline polymer contains an alicyclic structure. [4] The retardation film according to any one of [1] to [3], wherein the crystalline polymer is a hydrogenated product of a ring-opening polymer of dicyclopentadiene. [5] A first step of preparing a stretched film formed of a resin containing a polymer having crystallinity; A second step of contacting the stretched film with an organic solvent, The method for producing a retardation film, wherein tension is applied to the stretched film in the second step. [6] The method for producing a retardation film according to [5], wherein the polymer having crystallinity contains an alicyclic structure. [7] The method for producing a retardation film according to [5] or [6], wherein the crystalline polymer is a hydrogenated product of a ring-opening polymer of dicyclopentadiene. Effect of the Invention
[0012] According to the present invention, it is possible to provide a retardation film having excellent uniformity of in-plane retardation; and a production method by which a retardation film having excellent uniformity of in-plane retardation can be easily produced. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a plan view diagrammatically illustrating the stretched film obtained in Example 1. As shown in FIG. [Diagram 2] FIG. 2 is a plan view diagrammatically illustrating the jig used in Example 1. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0015] In the following description, the in-plane retardation Re of the film is a value expressed by "Re = (nx - ny) x d" unless otherwise specified. The in-plane birefringence of the film is a value expressed by "(nx - ny)" unless otherwise specified, and is therefore expressed by "Re / d". The thickness direction retardation Rth of the film is a value expressed by "Rth = [{(nx + ny) / 2} - nz] x d" unless otherwise specified. The thickness direction birefringence of the film is a value expressed by "[{(nx + ny) / 2} - nz]" unless otherwise specified, and is therefore expressed by "Rth / d". The NZ coefficient of the film is a value expressed by "(nx - nz) / (nx - ny)" unless otherwise specified, and is therefore expressed by "0.5 + Rth / Re". nx represents the refractive index in the direction perpendicular to the thickness direction of the film (in-plane direction) and giving the maximum refractive index. ny represents the refractive index in the in-plane direction of the film, perpendicular to the direction of nx; nz represents the refractive index in the thickness direction of the film; d represents the thickness of the film; the measurement wavelength is 590 nm unless otherwise specified.
[0016] In the following description, unless otherwise specified, the longitudinal and transverse directions of a film are perpendicular to each other and are both perpendicular to the thickness direction of the film. In a rectangular film, the direction parallel to one pair of opposing sides is usually the longitudinal direction, and the direction parallel to the other pair of sides is usually the transverse direction. In a long film, the longitudinal direction is usually the longitudinal direction, and the width direction is usually the transverse direction.
[0017] In the following description, a "long" film refers to a film having a length of 5 times or more, preferably 10 times or more, the width, specifically a film having a length that can be wound into a roll for storage or transportation. There is no particular upper limit on the length, but it is usually 100,000 times or less the width.
[0018] In the following description, the longitudinal direction of a long film is usually parallel to the film conveying direction in the production line. The MD direction is the film conveying direction in the production line, and is usually parallel to the longitudinal direction of the long film. The TD direction is a direction parallel to the film surface, perpendicular to the MD direction, and usually parallel to the width direction of the long film.
[0019] In the following description, unless otherwise specified, the directions of elements as "parallel," "vertical," and "orthogonal" may include an error within a range that does not impair the effect of the present invention, for example, within a range of ±5°.
[0020] [1. Overview of Retardation Film According to First Embodiment] The retardation film according to the first embodiment of the present invention is formed of a resin containing a polymer having crystallinity, and has a coefficient of variation CV(Re) of in-plane retardation at a measurement wavelength of 590 nm of 1.0% or less.
[0021] Such a retardation film has been difficult to realize with conventional techniques. In particular, when the optical anisotropy represented by retardation or birefringence is large, or when the degree of crystallization represented by the degree of crystallization is large, the in-plane retardation of the film formed from a resin containing a crystalline polymer tends to vary widely, so that it has been particularly difficult to realize the retardation film with conventional techniques. However, the present invention makes it possible to realize the retardation film for the first time.
[0022] The retardation film according to the first embodiment can improve the uniformity of the optical anisotropy even when it has a large optical anisotropy. Therefore, it is possible to realize a practical retardation film that is thin and has a desired retardation. In the past, technical means for solving the problem of making a retardation film thin while maintaining a desired retardation have been required, but it has been difficult to realize the technical means. In one aspect, the retardation film according to the first embodiment can be said to be the first to realize the above-mentioned technical means.
[0023] [2. Crystalline resin contained in the retardation film according to the first embodiment] The retardation film according to the first embodiment is formed of a resin containing a polymer having crystallinity. The term "polymer having crystallinity" refers to a polymer having a melting point Tm. That is, the term "polymer having crystallinity" refers to a polymer whose melting point can be observed by a differential scanning calorimeter (DSC). In the following description, a polymer having crystallinity may be referred to as a "crystalline polymer". Furthermore, a resin containing a crystalline polymer may be referred to as a "crystalline resin". This crystalline resin is preferably a thermoplastic resin.
[0024] The crystalline polymer preferably has a positive intrinsic birefringence. A polymer having a positive intrinsic birefringence means, unless otherwise specified, a polymer whose refractive index in the stretching direction is greater than that in the direction perpendicular thereto. The value of the intrinsic birefringence can be calculated from the dielectric constant distribution.
[0025] The crystalline polymer preferably contains an alicyclic structure. By using a crystalline polymer containing an alicyclic structure, the mechanical properties, heat resistance, transparency, low moisture absorption, dimensional stability and light weight of the retardation film can be improved. The polymer containing an alicyclic structure refers to a polymer containing an alicyclic structure in the molecule. Such a polymer containing an alicyclic structure can be, for example, a polymer obtained by polymerization reaction using a cyclic olefin as a monomer, or a hydrogenated product thereof.
[0026] Examples of the alicyclic structure include a cycloalkane structure and a cycloalkene structure. Among these, a cycloalkane structure is preferred because it is easy to obtain a retardation film having excellent properties such as thermal stability. The number of carbon atoms contained in one alicyclic structure is preferably 4 or more, more preferably 5 or more, and preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less. When the number of carbon atoms contained in one alicyclic structure is within the above range, mechanical strength, heat resistance, and moldability are highly balanced.
[0027] In the crystalline polymer containing an alicyclic structure, the ratio of the structural unit containing an alicyclic structure to all structural units is preferably 30% by weight or more, more preferably 50% by weight or more, and particularly preferably 70% by weight or more. By increasing the ratio of the structural unit containing an alicyclic structure as described above, heat resistance can be improved. The ratio of the structural unit containing an alicyclic structure to all structural units can be 100% by weight or less. In addition, in the crystalline polymer containing an alicyclic structure, the remainder other than the structural unit containing an alicyclic structure is not particularly limited and can be appropriately selected according to the purpose of use.
[0028] Examples of the crystalline polymer containing an alicyclic structure include the following polymer (α) to polymer (δ). Among these, polymer (β) is preferred because a retardation film having excellent heat resistance can be easily obtained. Polymer (α): A ring-opening polymer of a cyclic olefin monomer, which has crystallinity. Polymer (β): A hydrogenated product of polymer (α) and has crystallinity. Polymer (γ): An addition polymer of a cyclic olefin monomer, which has crystallinity. Polymer (δ): A hydrogenated polymer (γ) having crystallinity.
[0029] Specifically, the crystalline polymer containing an alicyclic structure is preferably a dicyclopentadiene ring-opening polymer having crystallinity, and a dicyclopentadiene ring-opening polymer hydrogenation product having crystallinity. Among them, a dicyclopentadiene ring-opening polymer hydrogenation product having crystallinity is particularly preferred. Here, the dicyclopentadiene ring-opening polymer refers to a polymer in which the ratio of dicyclopentadiene-derived structural units to all structural units is usually 50% by weight or more, preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 100% by weight.
[0030] The hydrogenated ring-opening polymer of dicyclopentadiene preferably has a high ratio of racemo dyads. Specifically, the ratio of racemo dyads in the repeating units of the hydrogenated ring-opening polymer of dicyclopentadiene is preferably 51% or more, more preferably 70% or more, and particularly preferably 85% or more. A high ratio of racemo dyads indicates high syndiotactic stereoregularity. Therefore, the higher the ratio of racemo dyads, the higher the melting point of the hydrogenated ring-opening polymer of dicyclopentadiene tends to be. The ratio of racemo-dyads is described in the Examples below. 13 It can be determined based on C-NMR spectrum analysis.
[0031] As the polymer (α) to polymer (δ), polymers obtained by the production method disclosed in WO 2018 / 062067 can be used.
[0032] The melting point Tm of the crystalline polymer is preferably 200° C. or higher, more preferably 230° C. or higher, and preferably 290° C. or lower. By using a crystalline polymer having such a melting point Tm, a retardation film having an even better balance between formability and heat resistance can be obtained.
[0033] Generally, a crystalline polymer has a glass transition temperature Tg. The specific glass transition temperature Tg of a crystalline polymer is not particularly limited, but is generally 85°C or higher and generally 170°C or lower.
[0034] The glass transition temperature Tg and melting point Tm of a polymer can be measured by the following method. First, the polymer is melted by heating, and the melted polymer is quenched with dry ice. Then, using this polymer as a test specimen, the glass transition temperature Tg and melting point Tm of the polymer can be measured using a differential scanning calorimeter (DSC) at a heating rate of 10° C. / min (heating mode).
[0035] The weight average molecular weight (Mw) of the crystalline polymer is preferably 1,000 or more, more preferably 2,000 or more, and is preferably 1,000,000 or less, more preferably 500,000 or less. A crystalline polymer having such a weight average molecular weight has an excellent balance between moldability and heat resistance.
[0036] The molecular weight distribution (Mw / Mn) of the crystalline polymer is preferably 1.0 or more, more preferably 1.5 or more, and is preferably 4.0 or less, more preferably 3.5 or less. Here, Mn represents the number average molecular weight. A crystalline polymer having such a molecular weight distribution has excellent moldability.
[0037] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the polymer can be measured in terms of polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as a developing solvent.
[0038] The degree of crystallinity of the crystalline polymer contained in the retardation film is not particularly limited, but is usually high to a certain degree. The specific range of the degree of crystallinity is preferably 10% or more, more preferably 15% or more, and particularly preferably 30% or more. The crystallinity of a crystalline polymer can be measured by X-ray diffraction.
[0039] The crystalline polymer may be used alone or in combination of two or more kinds in any ratio.
[0040] The proportion of the crystalline polymer in the crystalline resin is preferably 50% by weight or more, more preferably 70% by weight or more, and particularly preferably 90% by weight or more. When the proportion of the crystalline polymer is equal to or more than the lower limit of the above range, the birefringence expression and heat resistance of the retardation film can be improved. The upper limit of the proportion of the crystalline polymer can be 100% by weight or less.
[0041] The crystalline resin may contain optional components in addition to the crystalline polymer. Examples of the optional components include antioxidants such as phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants; light stabilizers such as hindered amine-based light stabilizers; waxes such as petroleum wax, Fischer-Tropsch wax, and polyalkylene wax; nucleating agents such as sorbitol-based compounds, metal salts of organic phosphoric acids, metal salts of organic carboxylic acids, kaolin, and talc; diaminostilbene derivatives, coumarin derivatives, and azole-based derivatives (e.g., benzoxazole derivatives, benzotriazole derivatives, and benzimide derivatives). Examples of the optional components include fluorescent brighteners such as benzothiazole derivatives, carbazole derivatives, pyridine derivatives, naphthalic acid derivatives, and imidazolone derivatives; ultraviolet absorbers such as benzophenone-based ultraviolet absorbers, salicylic acid-based ultraviolet absorbers, and benzotriazole-based ultraviolet absorbers; inorganic fillers such as talc, silica, calcium carbonate, and glass fibers; colorants; flame retardants; flame retardant assistants; antistatic agents; plasticizers; near-infrared absorbers; lubricants; fillers; and any polymer other than a crystalline polymer, such as a soft polymer. One type of optional component may be used alone, or two or more types may be used in combination at any ratio.
[0042] [3. Optical Properties of Retardation Film According to First Embodiment] The retardation film according to the first embodiment of the present invention has a coefficient of variation CV(Re) of in-plane retardation Re at a measurement wavelength of 590 nm within a specific range. Specifically, the coefficient of variation CV(Re) of in-plane retardation Re is usually 1.0% or less, preferably 0.8% or less, particularly preferably 0.5% or less, and ideally 0.0%. The coefficient of variation CV(Re) of in-plane retardation Re of the retardation film being within the specific range indicates that the in-plane retardation Re of the retardation film is excellent in uniformity. When such a retardation film is provided in an image display device, the display quality of the screen of the image display device can be made uniform regardless of the position within the screen.
[0043] The coefficient of variation means a value expressed as a percentage of the standard deviation based on the average value. Therefore, the coefficient of variation CV(Re) of the in-plane retardation Re of the retardation film can be obtained by dividing the standard deviation of the in-plane retardation Re of the retardation film by the average value of the in-plane retardation Re, and converting it into a percentage. The method of measuring the average value and standard deviation of the in-plane retardation Re of the retardation film will be described later.
[0044] A retardation film usually has a large birefringence in at least one of the in-plane direction and the thickness direction. -3 The average value of birefringence in the in-plane direction above and 1.0×10 -3 or the absolute value of the average value of birefringence in the thickness direction.
[0045] In detail, the average birefringence in the in-plane direction of the retardation film is usually 1.0 × 10 -3 More than 5.0×10 -3 More preferably, 15.0×10 -3 That's it. There is no upper limit. For example, 50.0×10 -3 Below, 30.0 x 10 -3 or less, or 25.0 x 10 -3However, the absolute value of the average value of birefringence in the thickness direction of the retardation film is 1.0×10 or less. -3 If it is equal to or greater than this range, the average birefringence in the in-plane direction of the retardation film may be outside the above range.
[0046] The absolute value of the average birefringence in the thickness direction of the retardation film is usually 1.0 × 10 -3 More than 3.0×10 -3 More preferably, 5.0×10 -3 That's it. There is no upper limit. For example, 20.0×10 -3 Below, 15.0 x 10 -3 or less, or 10.0 x 10 -3 However, the average birefringence in the in-plane direction of the retardation film may be 1.0×10 or less. -3 In the case where it is equal to or more than this range, the absolute value of the average value of the birefringence in the thickness direction of the retardation film may be outside the above range.
[0047] If a crystalline resin film is stretched and then heat-treated, a retardation film having a large birefringence as described above can be obtained, but the birefringence tends to vary widely. In contrast, the retardation film according to the first embodiment can achieve high uniformity by reducing the variation in birefringence while having a large birefringence as described above.
[0048] The degree of uniformity of the birefringence can be expressed by the standard deviation or coefficient of variation. The standard deviation of the birefringence in the in-plane direction of the retardation film is preferably 0.10×10 -3 Less than or equal to 0.08×10 -3 Less than 0.06×10 is particularly preferable. -3 The variation coefficient of birefringence in the in-plane direction of the retardation film is preferably 1.0% or less, more preferably 0.8% or less, particularly preferably 0.6% or less, and ideally 0%.
[0049] The standard deviation of birefringence in the thickness direction of the retardation film is preferably 0.10×10 -3Less than or equal to 0.08×10 -3 Less than 0.04 × 10, particularly preferably -3 The absolute value of the variation coefficient of birefringence in the thickness direction of the retardation film is preferably 1.0% or less, more preferably 0.9% or less, particularly preferably 0.8% or less, and ideally 0%.
[0050] The average value, standard deviation and variation coefficient of the birefringence of the retardation film can be measured by the following method. The retardation film is divided into three vertical sections and three horizontal sections, and nine measurement areas of the same area are set. Then, birefringence is measured in the center of each measurement area. The average value and standard deviation are calculated from the nine measured values obtained. The standard deviation is then divided by the average value and converted into a percentage to obtain the coefficient of variation. Among the birefringences, the birefringence in the in-plane direction can be obtained by measuring the in-plane retardation using a phase difference meter (e.g., "AxoScan OPMF-1" manufactured by AXOMETRICS) and dividing the measured value by the thickness. The birefringence in the thickness direction can be obtained by measuring the retardation in the thickness direction using a phase difference meter (e.g., "AxoScan OPMF-1" manufactured by AXOMETRICS) and dividing the measured value by the thickness.
[0051] The value of the in-plane retardation Re of the retardation film can be set depending on the application of the retardation film. The average value of the specific in-plane retardation Re of the retardation film is, for example, preferably 100 nm or more, more preferably 110 nm or more, particularly preferably 120 nm or more, and preferably 180 nm or less, more preferably 170 nm or less, particularly preferably 160 nm or less. In this case, the retardation film can function as a quarter-wave plate.
[0052] Furthermore, the average value of the specific in-plane retardation Re of the retardation film can be, for example, preferably 245 nm or more, more preferably 265 nm or more, particularly preferably 270 nm or more, and preferably 320 nm or less, more preferably 300 nm or less, particularly preferably 295 nm or less. In this case, the retardation film can function as a 1 / 2 wavelength plate.
[0053] Since the retardation film has excellent uniformity of the in-plane retardation Re, the standard deviation of the in-plane retardation Re can usually be made small. Specifically, the standard deviation of the in-plane retardation Re of the retardation film is preferably 4.0 nm or less, more preferably 3.0 nm or less, particularly preferably 2.0 nm or less, and ideally 0.0 nm.
[0054] The average value and standard deviation of the in-plane retardation Re of the retardation film can be measured by the following method. The retardation film is divided into three vertical sections and three horizontal sections, and nine measurement areas of the same area are set. Then, the in-plane retardation Re is measured at the center of each measurement area. The average value and standard deviation are calculated from the nine measured values obtained. The in-plane retardation Re can be measured using a retardation meter (for example, "AxoScan OPMF-1" manufactured by AXOMETRICS).
[0055] The retardation Rth value in the thickness direction of the retardation film can be set according to the application of the retardation film. The absolute value of the average value of the specific retardation Rth in the thickness direction of the retardation film can be preferably 50 nm or more, more preferably 55 nm or more, and particularly preferably 60 nm or more. The upper limit can be 10000 nm or less.
[0056] The retardation film is usually excellent in the uniformity of the retardation Rth in the thickness direction. Therefore, the standard deviation and the coefficient of variation CV(Rth) of the retardation Rth in the thickness direction of the retardation film are preferably small. Specifically, the standard deviation of the retardation Rth in the thickness direction of the retardation film is preferably 2.5 nm or less, more preferably 2.0 nm or less, particularly preferably 1.5 nm or less, and ideally 0.0 nm. In addition, the absolute value of the coefficient of variation CV(Rth) of the retardation Rth in the thickness direction of the retardation film is preferably 1.0% or less, more preferably 0.9% or less, particularly preferably 0.8% or less, and ideally 0%.
[0057] The average value, standard deviation and coefficient of variation of the retardation Rth in the thickness direction of the retardation film can be measured by the following method. The retardation film is divided into three vertical sections and three horizontal sections, and nine measurement areas of the same area are set. Then, the thickness direction retardation Rth is measured at the center of each measurement area. The average value and standard deviation are calculated from the nine measured values obtained. The standard deviation is divided by the average value and converted into a percentage to obtain the coefficient of variation. The thickness direction retardation Re can be measured using a retardation meter (for example, "AxoScan OPMF-1" manufactured by AXOMETRICS).
[0058] The value of the NZ coefficient of the retardation film can be set according to the application of the retardation film. The specific average value of the NZ coefficient of the retardation film is preferably greater than 0.0, more preferably 0.5 or more, particularly preferably 0.6 or more, and preferably less than 1.0. Since a retardation film having an average value of the NZ coefficient greater than 0.0 and less than 1.0 was difficult to manufacture by conventional techniques, a retardation film having an average value of the NZ coefficient in the above range is industrially useful. When a retardation film having an average value of the NZ coefficient in the above range is provided in a display device, it is possible to improve the display quality such as the viewing angle, contrast, and image quality of the display device.
[0059] Retardation film usually has excellent uniformity of NZ coefficient.Therefore, the variation coefficient of NZ coefficient of retardation film is preferably small.Specifically, the variation coefficient of NZ coefficient of retardation film is preferably 1.0% or less, more preferably 0.7% or less, particularly preferably 0.5% or less, and ideally 0.0%.
[0060] The average value and the coefficient of variation of the NZ coefficient of the retardation film can be measured by the following method. The retardation film is divided into three vertical sections and three horizontal sections, and nine measurement areas of the same area are set. Then, in the center of each measurement area, the in-plane retardation Re and the retardation in the thickness direction Rth are measured, and the NZ coefficient is calculated by "NZ coefficient = 0.5 + Rth / Re". The average value and standard deviation are calculated from the nine calculated values obtained. In addition, the standard deviation is divided by the average value and converted into a percentage to obtain the coefficient of variation. The in-plane retardation Re and the retardation in the thickness direction Re can be measured by the method described above.
[0061] Since the retardation film is an optical film, it is preferable that the retardation film has high transparency. Specifically, the retardation film has a total light transmittance of preferably 80% or more, more preferably 85% or more, and particularly preferably 88% or more. The total light transmittance of the retardation film can be measured in the wavelength range of 400 nm to 700 nm using an ultraviolet-visible spectrometer.
[0062] The haze of the retardation film is preferably less than 1.0%, more preferably less than 0.8%, particularly preferably less than 0.5%, and ideally 0.0%. The haze of the retardation film can be measured using a haze meter (for example, "NDH5000" manufactured by Nippon Denshoku Industries Co., Ltd.).
[0063] [4. Organic Solvent That Can Be Included in the Retardation Film According to the First Embodiment] The retardation film according to the first embodiment of the present invention may contain an organic solvent. This organic solvent is usually incorporated into the film in the second step of the production method described in the second embodiment.
[0064] The organic solvent taken into the film in the second step may penetrate into the polymer. Therefore, even if drying is performed at a temperature equal to or higher than the boiling point of the organic solvent, it is difficult to completely remove the solvent. Therefore, the retardation film may contain an organic solvent.
[0065] The organic solvent may be one that does not dissolve the crystalline polymer. Preferred organic solvents include, for example, hydrocarbon solvents such as toluene, limonene, and decalin; and carbon disulfide. The type of organic solvent may be one type or two or more types.
[0066] The ratio of the organic solvent contained in the retardation film to the weight of 100% of the retardation film (solvent content) is preferably 10% by weight or less, more preferably 5% by weight or less, even more preferably 4% by weight or less, and particularly preferably 0.1% by weight or less. The lower limit is preferably closer to zero, and is usually equal to or greater than the detection limit. The lower limit is preferably 0.01 ppm or more.
[0067] The solvent content of the retardation film can be measured by the measurement method described in the Examples.
[0068] [5. Thickness and shape of retardation film according to the first embodiment] The thickness d of the retardation film according to the first embodiment of the present invention can be appropriately set according to the application of the retardation film. The specific thickness d of the retardation film is preferably 5 μm or more, more preferably 10 μm or more, particularly preferably 20 μm or more, and preferably 200 μm or less, more preferably 100 μm or less, particularly preferably 50 μm or less. When the thickness d of the retardation film is equal to or more than the lower limit of the above range, the handling property can be improved and the strength can be increased. In addition, when the thickness d of the retardation film is equal to or less than the upper limit, it is easy to wind up a long retardation film.
[0069] The retardation film may be a sheet of film or a long film.
[0070] [6. Method for producing retardation film according to the first embodiment] The retardation film according to the first embodiment described above can be produced by a production method described in a second embodiment described later.
[0071] [7. Method for producing retardation film according to the second embodiment] The method for producing a retardation film according to the second embodiment of the present invention includes a first step of preparing a stretched film made of a crystalline resin containing a crystalline polymer, and a second step of contacting the stretched film with an organic solvent. In this production method, the stretched film is usually brought into contact with the organic solvent in the second step, whereby the birefringence of the stretched film changes, and a retardation film having desired optical properties is obtained.
[0072] In addition, in this manufacturing method, tension is applied to the stretched film in the second step. When the stretched film is contacted with an organic solvent in such a tensioned state, a retardation film having a small coefficient of variation CV(Re) of in-plane retardation can be easily manufactured.
[0073] The present inventors speculate that the mechanism by which a retardation film having a small coefficient of variation CV(Re) of in-plane retardation can be obtained by this manufacturing method is as follows, although the technical scope of the present invention is not limited by the mechanism described below.
[0074] The molecules of the crystalline polymer contained in the stretched film formed of the crystalline resin are oriented to a degree according to the stretching conditions. Usually, the stretching is performed in the in-plane direction perpendicular to the thickness direction of the film, so that most of the molecules of the crystalline polymer can be oriented in the in-plane direction of the stretched film. When the stretched film containing the molecules of the crystalline polymer oriented in this way is contacted with an organic solvent in the second step, the organic solvent penetrates into the stretched film. Due to the action of the penetrated organic solvent, micro-Brownian motion occurs in the molecules of the crystalline polymer in the film, and the orientation of the molecules in the film further progresses, and the degree of orientation increases. According to the study by the present inventor, it is considered that when the orientation of the molecules progresses, a solvent-induced crystallization phenomenon of the crystalline polymer may occur. When the degree of orientation of the molecules increases in this way, the birefringence of the film changes, and thus the retardation may also change. Usually, the change in retardation progresses so that the in-plane retardation Re increases.
[0075] However, when the orientation of the molecules progresses, the molecules of the crystalline polymer may move, so that stress may occur in the film. Such stress may easily cause bias in the film. If such a bias in the stress occurs, the orientation state of the molecules of the crystalline polymer may be affected by the biased stress, so that the orientation state may vary. In contrast, in the state where tension is applied to the film, as in the second step of the manufacturing method according to the second embodiment, the influence of the bias in the stress can be reduced, so that the variation in the orientation state caused by contact with the organic solvent can be reduced. Therefore, the uniformity of the optical properties of the obtained retardation film can be improved, so that the coefficient of variation CV (Re) of in-plane retardation can be reduced.
[0076] The surface area of a stretched film is generally large on the front and back surfaces, which are the main surfaces. Therefore, the penetration speed of the organic solvent is high in the thickness direction through the front or back surface. Then, some of the molecules of the crystalline polymer can be oriented in the thickness direction by the penetration of the organic solvent. Then, the refractive index nz in the thickness direction of the film increases, so that the average value of the NZ coefficient of the retardation film can be in the range of more than 0.0 and less than 1.0.
[0077] The manufacturing method according to the second embodiment of the present invention may be particularly beneficial when a stretched film with low birefringence is used. In addition, since a retardation film manufactured using a stretched film with low birefringence generally has low retardation or birefringence, the manufacturing method according to the second embodiment of the present invention may be particularly beneficial when a retardation film with low retardation or birefringence is manufactured. According to the study by the present inventor, the smaller the birefringence of a stretched film formed of a crystalline resin, the greater the variation in birefringence caused in the stretched film by contact with an organic solvent, and therefore the uniformity of the optical properties of the obtained retardation film is likely to be low. In contrast, in the above-mentioned second embodiment, even when a stretched film with low birefringence is used, the uniformity of the optical properties of the obtained retardation film can be improved. In this way, when a stretched film with low birefringence is used or a retardation film with low retardation or birefringence is manufactured, the manufacturing method according to the second embodiment of the present invention has a remarkable significance in that it can solve new problems that have not been found before. The present inventors speculate that the mechanism for solving such a new problem is as follows, however, the technical scope of the present invention is not limited to the mechanism described below.
[0078] Generally, when a stretched film has a large birefringence, the degree of orientation of the molecules of the crystalline polymer contained in the stretched film is large. When the degree of orientation is large, when the orientation of the molecules progresses due to contact with an organic solvent, the range in which the molecules can move is restricted due to the progress of the orientation, so the range of change in the orientation state is narrow. Therefore, the degree of freedom of the change in the orientation state caused by contact with an organic solvent for each molecule is relatively small, and as a result, the variation in the orientation state is small, and the variation in the birefringence can be relatively small. However, when a stretched film has a small birefringence, the degree of orientation of the molecules of the crystalline polymer contained in the stretched film is generally small. When the degree of orientation is small, when the orientation of the molecules progresses due to contact with an organic solvent, the range in which the molecules can move due to the progress of orientation is wide, so the range of change in the orientation state is wide. Therefore, the degree of freedom of the change in the orientation state caused by contact with an organic solvent for each molecule is relatively large, and as a result, the variation in the orientation state becomes large, and the variation in the birefringence may become relatively large. Therefore, when no tension is applied during contact between the organic solvent and the stretched film, the smaller the birefringence of the stretched film, the lower the uniformity of the optical properties of the resulting retardation film. This tendency may be the same in the method of producing a retardation film having a large retardation by subjecting the stretched film to a heat treatment.
[0079] On the other hand, as in the second step of the manufacturing method according to the second embodiment, when the film is contacted with an organic solvent under tension, the degree of freedom of the change in the orientation state caused by contact with the organic solvent in each molecule can be effectively reduced by the tension. Therefore, even when using a stretched film with low birefringence or manufacturing a retardation film with low retardation or birefringence, the manufacturing method according to the second embodiment can manufacture a retardation film with high uniformity of optical properties.
[0080] The method for producing a retardation film according to the second embodiment of the present invention may further include any step in combination with the above-mentioned first and second steps. For example, the method for producing a retardation film may include a third step of drying the obtained retardation film after the second step.
[0081] [8. First step: Preparation of stretched film] In the first step, a stretched film formed of a crystalline resin containing a crystalline polymer is prepared. There is no limitation on the method of preparing the stretched film. The first step may include, for example, a step of preparing a resin film formed of a crystalline resin and a step of stretching the resin film to obtain a stretched film. In the following description, the resin film before stretching may be appropriately referred to as a "film before stretching."
[0082] The crystalline resin as the material of the pre-stretched film and the stretched film may be the same as the crystalline resin described in the first embodiment. However, the crystallinity of the crystalline polymer contained in the pre-stretched film and the stretched film is preferably small. The specific crystallinity is preferably less than 10%, more preferably less than 5%, and particularly preferably less than 3%. If the crystallinity of the crystalline polymer contained in the pre-stretched film and the stretched film before contacting with an organic solvent is low, the orientation of many molecules of the crystalline polymer can be promoted by contact with the organic solvent, so that the birefringence and retardation can be adjusted in a wide range.
[0083] There is no limitation on the method for producing the pre-stretched film from the crystalline resin. Since the pre-stretched film does not contain an organic solvent, the method for producing the pre-stretched film is preferably a resin molding method such as injection molding, extrusion molding, press molding, inflation molding, blow molding, calendar molding, cast molding, compression molding, etc. Among these, the extrusion molding method is preferred because it is easy to control the thickness.
[0084] The manufacturing conditions in the extrusion molding method are preferably as follows. The cylinder temperature (molten resin temperature) is preferably Tm or higher, more preferably "Tm+20°C" or higher, and preferably "Tm+100°C" or lower, more preferably "Tm+50°C" or lower. The cooling body that the molten resin extruded into a film first comes into contact with is not particularly limited, but a cast roll is usually used. The cast roll temperature is preferably "Tg-50°C" or higher, preferably "Tg+70°C" or lower, more preferably "Tg+40°C" or lower. Furthermore, the cooling roll temperature is preferably "Tg-70°C" or higher, more preferably "Tg-50°C" or higher, and preferably "Tg+60°C" or lower, more preferably "Tg+30°C" or lower. When a pre-stretched film is manufactured under such conditions, a pre-stretched film having a thickness of 1 μm to 1 mm can be easily manufactured. Here, "Tm" represents the melting point of the crystalline polymer, and "Tg" represents the glass transition temperature of the crystalline polymer.
[0085] The first step may include a step of preparing a pre-stretch film and then performing a pre-heating treatment to heat the pre-stretch film to a stretching temperature before stretching the pre-stretch film. Usually, the pre-heating temperature and the stretching temperature are the same, but they may be different. The pre-heating temperature is preferably T1-10°C or higher, more preferably T1-5°C or higher, and preferably T1+5°C or lower, more preferably T1+2°C or lower, relative to the stretching temperature T1. The pre-heating time is optional, and is preferably 1 second or higher, more preferably 5 seconds or higher, and preferably 60 seconds or lower, more preferably 30 seconds or lower.
[0086] The first step may include preparing a pre-stretched film, optionally preheating the film, and then stretching the pre-stretched film. Usually, the stretching orients the molecules of the crystalline polymer contained in the pre-stretched film in a direction corresponding to the stretching direction to obtain a stretched film.
[0087] There is no limitation on the stretching direction, and examples thereof include the longitudinal direction, the width direction, and the oblique direction. Here, the oblique direction refers to a direction perpendicular to the thickness direction, and is neither parallel nor perpendicular to the width direction. The stretching direction may be one direction or two or more directions. Thus, examples of the stretching method include uniaxial stretching methods such as a method of uniaxially stretching a pre-stretched film in the longitudinal direction (longitudinal uniaxial stretching method) and a method of uniaxially stretching a pre-stretched film in the width direction (transverse uniaxial stretching method); biaxial stretching methods such as a simultaneous biaxial stretching method in which a pre-stretched film is stretched in the longitudinal direction and simultaneously stretched in the width direction, and a sequential biaxial stretching method in which a pre-stretched film is stretched in one of the longitudinal direction and the width direction and then stretched in the other direction; and a method of stretching a pre-stretched film in an oblique direction (oblique stretching method).
[0088] The stretching ratio is preferably 1.1 times or more, more preferably 1.2 times or more, and preferably 20.0 times or less, more preferably 10.0 times or less, even more preferably 5.0 times or less, and particularly preferably 2.0 times or less. It is desirable to appropriately set the specific stretching ratio according to factors such as the optical properties, thickness, and strength of the retardation film to be produced. When the stretching ratio is equal to or greater than the lower limit of the above range, the birefringence can be significantly changed by stretching. In addition, when the stretching ratio is equal to or less than the upper limit of the above range, the direction of the slow axis can be easily controlled and the breakage of the film can be effectively suppressed.
[0089] The stretching temperature is preferably "Tg+5°C" or higher, more preferably "Tg+10°C" or higher, and preferably "Tg+100°C" or lower, more preferably "Tg+90°C" or lower. Here, "Tg" represents the glass transition temperature of the crystalline polymer. When the stretching temperature is equal to or higher than the lower limit of the above range, the crystalline resin can be sufficiently softened to perform uniform stretching. When the stretching temperature is equal to or lower than the upper limit of the above range, the hardening of the crystalline resin due to the progress of crystallization of the crystalline polymer can be suppressed, so that the stretching can be performed smoothly, and large birefringence can be expressed by stretching. Furthermore, the haze of the obtained stretched film can usually be reduced to increase transparency.
[0090] The optical properties of the resulting stretched film are preferably set according to the optical properties of the retardation film to be produced so that a retardation film having desired optical properties is obtained.
[0091] For example, the average in-plane retardation Re of the stretched film may be preferably 10 nm or more, more preferably 20 nm or more, particularly preferably 30 nm or more, and may be preferably 150 nm or less, more preferably 140 nm or less, particularly preferably 130 nm or less.
[0092] For example, the absolute value of the average retardation Rth in the thickness direction of the stretched film can be preferably 10 nm or more, more preferably 20 nm or more, and particularly preferably 30 nm or more, and can be preferably 150 nm or less, more preferably 140 nm or less, and particularly preferably 130 nm or less.
[0093] For example, the average birefringence in the in-plane direction of the stretched film is preferably 1.0×10 -3 More preferably, 1.3×10 -3 More preferably, 1.5×10 -3 or more, and preferably 10.0×10 -3 Less than or equal to 8.0×10 -3 Less than 5.0×10 -3 It can be the following:
[0094] For example, the absolute value of the average value of birefringence in the thickness direction of the stretched film is preferably 1.0×10 -3 More preferably, 1.3×10 -3 More preferably, 1.5×10 -3 or more, and preferably 10.0×10 -3 Less than or equal to 8.0×10 -3 Less than 5.0×10 -3 It can be the following:
[0095] The average in-plane retardation Re, the average thickness direction retardation Rth, the average in-plane birefringence, and the average thickness direction birefringence of the stretched film can be measured by the following method. The stretched film is divided into three sections in the longitudinal direction and three sections in the transverse direction, and nine measurement areas of equal area are set. Then, in the center of each measurement area, the in-plane retardation Re, the thickness direction retardation Rth, the in-plane birefringence, and the thickness direction birefringence are measured. The average values are calculated from the obtained measured values. The in-plane retardation Re, the thickness direction retardation Re, the in-plane birefringence, and the thickness direction birefringence can be measured by the method described above.
[0096] The stretched film preferably has a small content of organic solvent, and more preferably does not contain any organic solvent. The ratio of the organic solvent contained in the stretched film to 100% by weight of the stretched film (solvent content) is preferably 1.0% or less, more preferably 0.5% or less, particularly preferably 0.1% or less, and ideally 0.0%. Since the amount of organic solvent contained in the stretched film as a film before contact with the organic solvent is small, the orientation of many crystalline polymer molecules can be promoted by contact with the organic solvent, and therefore the birefringence and retardation can be adjusted in a wide range.
[0097] The solvent content of the stretched film can be measured by density.
[0098] The haze of the stretched film is preferably less than 1.0%, preferably less than 0.8%, more preferably less than 0.5%, and ideally 0.0%. The smaller the haze of the stretched film, the easier it is to reduce the haze of the resulting retardation film.
[0099] The thickness of the stretched film is preferably set according to the thickness of the retardation film to be produced. Usually, the thickness is increased by contacting with an organic solvent in the second step. Therefore, the thickness of the stretched film may be set in consideration of the change in thickness in the second step and subsequent steps.
[0100] The stretched film may be a sheet film, but is preferably a long film. By using a long stretched film, the retardation film can be continuously produced by the roll-to-roll method, so that the productivity of the retardation film can be effectively improved.
[0101] [9. Second step: Contact of stretched film with organic solvent] In the second step, the stretched film prepared in the first step is brought into contact with an organic solvent, whereby the optical properties of the stretched film are adjusted to obtain a retardation film having desired optical properties.
[0102] As the organic solvent, a solvent that can penetrate into the stretched film without dissolving the crystalline polymer contained in the stretched film can be used, and examples thereof include hydrocarbon solvents such as toluene, limonene, and decalin; and carbon disulfide. The type of organic solvent may be one type or two or more types.
[0103] Examples of the method for contacting the stretched film with the organic solvent include a spray method in which the organic solvent is sprayed onto the stretched film, a coating method in which the organic solvent is applied onto the stretched film, and an immersion method in which the stretched film is immersed in the organic solvent. Among these, the immersion method is preferred because it allows easy continuous contact.
[0104] The temperature of the organic solvent brought into contact with the stretched film may be any temperature within a range in which the organic solvent can maintain a liquid state, and therefore may be set within a range from the melting point to the boiling point of the organic solvent.
[0105] The time for contacting the stretched film with the organic solvent is not particularly specified, but is preferably 0.5 seconds or more, more preferably 1.0 seconds or more, particularly preferably 5.0 seconds or more, and preferably 120 seconds or less, more preferably 80 seconds or less, particularly preferably 60 seconds or less. When the contact time is equal to or more than the lower limit of the above range, the birefringence and retardation can be effectively adjusted by contact with the organic solvent. On the other hand, even if the immersion time is extended, the adjustment amount of the birefringence and retardation tends not to change significantly. Therefore, when the contact time is equal to or less than the upper limit of the above range, the productivity can be increased without impairing the quality of the retardation film.
[0106] The second step is performed in a state where the stretched film is tensioned. By contacting the organic solvent with the stretched film in a state where the stretched film is tensioned, the uniformity of the optical properties of the resulting retardation film can be improved, and therefore the coefficient of variation CV(Re) of the in-plane retardation Re can be reduced.
[0107] The magnitude of the tension applied to the stretched film in the second step is preferably set within a range in which the stretched film is not substantially stretched by the tension. "Substantially stretched" generally means that the stretching ratio in any direction of the film is 1.1 times or more. The specific range of the tension is preferably 5 N / m or more, more preferably 10 N / m or more, particularly preferably 15 N / m or more, and preferably 200 N / m or less, more preferably 150 N / m or less, particularly preferably 100 N / m or less. The unit of tension "N / m" represents the magnitude of the tension per meter of the film dimension in the direction perpendicular to the tension direction.
[0108] The number of tension directions as the direction of tension applied to the stretched film may be one or more. Usually, tension is applied in an in-plane direction perpendicular to the thickness direction of the stretched film. Therefore, the tension direction may be one or more in-plane directions. For example, when the stretched film is a sheet film, the tension direction may be one or both of the longitudinal direction and the transverse direction of the film. Also, for example, when the stretched film is a long film, the tension direction may be one or both of the longitudinal direction and the width direction of the film. Among them, from the viewpoint of effectively increasing the uniformity of the optical properties of the retardation film and reducing the coefficient of variation CV(Re) of the in-plane retardation Re, the number of tension directions is preferably one.
[0109] When applying tension to the stretched film as described above, for example, the stretched film may be held by an appropriate holder and tensioned by pulling the stretched film with the holder. The holder may be capable of continuously holding the entire length of the side of the stretched film, or may be capable of holding it intermittently at intervals. For example, the side of the stretched film may be held intermittently by holders arranged at predetermined intervals.
[0110] It is preferable that at least two sides of the stretched film are held and tension is applied. In this case, tension is applied to the stretched film in the area between the held sides, thereby improving the uniformity of the optical properties of the retardation film. In order to improve the uniformity of the optical properties over a wide area, it is preferable to hold the sides including the two opposing sides of the stretched film and apply tension to the area between the held sides. For example, in a rectangular sheet of stretched film, the uniformity of the optical properties can be improved over the entire surface of the retardation film obtained from the stretched film by holding two opposing sides (e.g., the long sides or the short sides) and applying tension to the area between the two sides. In addition, in a long stretched film, the uniformity of the optical properties can be improved over the entire surface of the retardation film obtained from the stretched film by holding two sides (i.e., the long sides) at the ends in the width direction and applying tension to the area between the two sides.
[0111] It is preferable that the holder does not come into contact with the stretched film at any portion other than the sides of the stretched film. By using such a holder, a retardation film having superior smoothness can be obtained.
[0112] In addition, the holders are preferably ones that can fix the relative positions of the holders while they are holding the stretched film, and such holders do not move relative to each other, making it easier to suppress substantial stretching of the stretched film.
[0113] Suitable holders include, for example, holders for rectangular stretched films, such as grippers such as clips that are provided at a predetermined interval on a frame material and can grip the stretched film. Also, for example, holders for holding two sides at the ends in the width direction of a long stretched film include grippers that are provided on a tenter stretching machine and can grip the stretched film.
[0114] When a long stretched film is used, the side at the end in the longitudinal direction of the stretched film (i.e., the short side) may be held, but instead of holding the side, both sides in the longitudinal direction of the area in which the stretched film is subjected to the second process may be held. For example, a holding device capable of holding the stretched film and applying tension to it may be provided on both sides in the longitudinal direction of the area in which the stretched film is subjected to the second process. Examples of such a holding device include a combination of two rolls. By applying tension such as transport tension to the stretched film using the combination, the uniformity of the optical properties can be increased in the area in which the second process is performed. Therefore, if the combination is used as a holding device, the stretched film can be held while being transported in the longitudinal direction, and therefore a retardation film can be efficiently manufactured.
[0115] By contacting with the organic solvent in the second step, the optical properties of the stretched film, such as the in-plane retardation Re, the thickness retardation Rth, the birefringence in the in-plane direction, and the birefringence in the thickness direction, may change. Therefore, there may be a difference according to the amount of change between the optical properties of the stretched film as a film before contacting with the organic solvent and the optical properties of the retardation film as a film after contacting with the organic solvent.
[0116] For example, the change in the in-plane retardation Re due to contact with an organic solvent can be expressed as the difference between the average in-plane retardation Re of the stretched film and the average in-plane retardation Re of the retardation film. The specific range of this difference is preferably 50 nm or more, more preferably 100 nm or more, particularly preferably 150 nm or more, and preferably 1000 nm or less, more preferably 800 nm or less, particularly preferably 500 nm or less.
[0117] For example, the change in the retardation Rth in the thickness direction due to contact with an organic solvent can be expressed as the difference between the average retardation Rth in the thickness direction of the stretched film and the average retardation Rth in the thickness direction of the retardation film. The specific range of this difference is preferably 10 nm or more, more preferably 30 nm or more, particularly preferably 50 nm or more, and preferably 1000 nm or less, more preferably 500 nm or less, particularly preferably 300 nm or less.
[0118] For example, the change in in-plane birefringence due to contact with an organic solvent can be expressed as the difference between the average in-plane birefringence of the stretched film and the average in-plane birefringence of the retardation film. The specific range of this difference is preferably 1×10 -3 More preferably, 3×10 -3 More preferably, 5×10 -3 or more, and preferably 50×10 -3 Less than or equal to 40×10 -3 Below, particularly preferably 30×10 -3 It can be the following:
[0119] For example, the change in birefringence in the thickness direction due to contact with an organic solvent can be expressed as the difference between the average value of birefringence in the thickness direction of a stretched film and the average value of birefringence in the thickness direction of a retardation film. The specific range of this difference is preferably 0.2×10 -3 More preferably, 0.6×10 -3 More preferably, 1.0×10 -3 or more, and preferably 50×10 -3 Less than or equal to 40×10 -3 Below, particularly preferably 30×10 -3 It can be the following:
[0120] The organic solvent contacting the stretched film may penetrate into the stretched film, thereby increasing the film thickness in the second step. In this case, the lower limit of the thickness change rate may be, for example, 10% or more, 20% or more, or 30% or more. The upper limit of the thickness change rate may be, for example, 80% or less, 50% or less, or 40% or less. The thickness change rate is a ratio obtained by dividing the difference between the thickness of the retardation film and the thickness of the stretched film by the thickness of the stretched film.
[0121] As described above, in the second step, the optical properties of the stretched film are adjusted with high uniformity, thereby obtaining a retardation film having desired optical properties. The retardation film thus obtained may be used as it is, or may be subjected to any further steps.
[0122] [10. Optional process] The method for producing a retardation film according to the second embodiment may further include any step in combination with the above-mentioned steps. For example, the method for producing a retardation film may include a step of removing the organic solvent attached to the retardation film after the second step. Examples of the method for removing the organic solvent include drying and wiping. Among them, drying is preferable from the viewpoint of quickly removing the organic solvent to obtain a retardation film having stable characteristics.
[0123] From the viewpoint of rapid drying, the drying temperature is preferably 50° C. or higher, more preferably 60° C. or higher, and particularly preferably 80° C. or higher. From the viewpoint of suppressing thermal orientation relaxation and maintaining uniformity of optical properties, the drying temperature is preferably Tg+100° C. or lower, more preferably Tg+80° C. or lower, and particularly preferably Tg+50° C. or lower. Here, "Tg" represents the glass transition temperature of the crystalline polymer.
[0124] From the viewpoint of sufficiently removing the organic solvent from the retardation film, the drying time is preferably 5 minutes or more, more preferably 10 minutes or more, and particularly preferably 30 minutes or more. From the viewpoint of shortening the time required for manufacturing the retardation film and improving the manufacturing efficiency, the drying time is preferably 5 hours or less, more preferably 3 hours or less, and particularly preferably 2 hours or less.
[0125] When the drying is performed, it is preferable to apply tension to the retardation film. By performing drying under tension, the uniformity of the optical properties of the retardation film can be effectively increased. The range of the magnitude of the tension applied to the retardation film during drying can be the same as the range of the magnitude of the tension applied to the stretched film in the second step. In addition, the number of directions of the tension applied to the retardation film may be one or more, the same as the directions of the tension applied to the stretched film in the second step.
[0126] When applying tension to the retardation film during drying, for example, the retardation film may be held by an appropriate holder, and the retardation film may be pulled by the holder to apply tension. For example, the same holder as that described as the holder that can be used to apply tension to the stretched film in the second step may be used as the holder. From the viewpoint of achieving efficient retardation film production by reducing the number of times the holder is attached and detached, it is preferable not to remove the holder after the second step, but to dry the retardation film while maintaining the state in which the holder applies tension to it, and then to remove the holder from the retardation film.
[0127] According to the above-mentioned manufacturing method, a long retardation film can be manufactured using a long stretched film. The manufacturing method of the retardation film may include a step of winding the long retardation film thus manufactured into a roll. Furthermore, the manufacturing method of the retardation film may include a step of cutting the long retardation film into a desired shape.
[0128] [11. Retardation film manufactured by the manufacturing method according to the second embodiment] According to the manufacturing method of the second embodiment, the optical properties of the stretched film can be adjusted with high uniformity by a simple process of contacting the stretched film with an organic solvent while applying tension to the stretched film. Therefore, a retardation film having excellent uniformity of optical properties can be easily manufactured, and for example, a retardation film having a coefficient of variation CV(Re) of in-plane retardation Re of 1.0% or less can be easily obtained.
[0129] In addition, by contacting the stretched film with an organic solvent, the optical properties of the stretched film can be adjusted over a wide range, so that a retardation film having a large optical anisotropy, which has been difficult to achieve in the past, can be manufactured. For example, it is possible to manufacture a retardation film having a large parameter representing the optical anisotropy, such as the average in-plane retardation, the average thickness retardation, the average in-plane birefringence, or the average thickness birefringence.
[0130] The coefficient of variation CV(Re) of the in-plane retardation Re of the retardation film manufactured by the manufacturing method according to the second embodiment may be the same as the coefficient of variation CV(Re) of the in-plane retardation Re of the retardation film according to the first embodiment. Furthermore, the retardation film manufactured by the manufacturing method according to the second embodiment may have the same properties as the retardation film according to the first embodiment, other than the coefficient of variation CV(Re) of the in-plane retardation Re. Therefore, the retardation film manufactured by the manufacturing method according to the second embodiment may have the same properties as the retardation film according to the first embodiment, such as the crystalline resin contained in the retardation film; the average value, standard deviation, and coefficient of variation of the birefringence in the in-plane direction of the retardation film; the absolute value of the average value, standard deviation, and absolute value of the coefficient of variation of the birefringence in the thickness direction of the retardation film; the average value and standard deviation of the in-plane retardation Re of the retardation film; the absolute value of the average value, standard deviation, and absolute value of the coefficient of variation CV(Rth) of the retardation in the thickness direction of the retardation film; the average value and coefficient of variation of the NZ coefficient of the retardation film; the total light transmittance and haze of the retardation film; the amount of organic solvent contained in the retardation film; and the thickness of the retardation film.
[0131] [12.Applications] The retardation film according to the first embodiment and the retardation film manufactured by the manufacturing method according to the second embodiment described above can be provided in, for example, a display device. In this case, the retardation film can improve the uniformity of display quality such as the viewing angle, contrast, and image quality of an image displayed on the display device. EXAMPLES
[0132] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the examples shown below, and can be modified and carried out as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto.
[0133] In the following description, the units "%" and "parts" are by weight unless otherwise specified. The operations described below were performed at room temperature and pressure unless otherwise specified. In the following description, the wavelength for measuring retardation and birefringence was 590 nm unless otherwise specified.
[0134] [Evaluation method] (Method of measuring weight average molecular weight Mw and number average molecular weight Mn of polymer) The weight average molecular weight Mw and number average molecular weight Mn of the polymer were measured as polystyrene equivalent values using a gel permeation chromatography (GPC) system (Tosoh Corporation, "HLC-8320"). In the measurement, an H-type column (Tosoh Corporation) was used as the column, and tetrahydrofuran was used as the solvent. The temperature during the measurement was 40°C.
[0135] (Method for measuring hydrogenation rate of polymer) The hydrogenation rate of the polymer is 4 as a solvent at 145°C, 1 Measured by H-NMR measurement.
[0136] (Method of measuring glass transition temperature Tg and melting point Tm) The glass transition temperature Tg and melting point Tm of the polymer were measured as follows. First, the polymer was melted by heating, and the melted polymer was quenched with dry ice. Then, the glass transition temperature Tg and melting point Tm of the polymer were measured using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min (heating mode) using the polymer as a test specimen.
[0137] (Method for measuring the ratio of racemo-dyads in polymers) The ratio of racemo-dyads in the polymer was determined as follows. 4 The inverse-gated decoupling method was applied to the polymer at 200°C using 13 C-NMR measurements were performed. 13The results of C-NMR measurement showed that o-dichlorobenzene-d 4 Using the peak at 127.5 ppm as the reference shift, the signal at 43.35 ppm from the meso-dyad and the signal at 43.43 ppm from the racemo-dyad were identified. The ratio of the racemo-dyads in the polymer was calculated based on the intensity ratio of these signals.
[0138] (Method of measuring film thickness) The thickness of the film was measured using a contact thickness meter (manufactured by MITUTOYO, Code No. 543-390).
[0139] (Method for measuring the solvent content of a retardation film) A rectangular stretched film (film before contact with the solvent) was produced by the same method as in each of the examples and comparative examples. This stretched film was cut into a rectangle of the same dimensions as the retardation film to obtain a reference film. The weight of this reference film was measured by thermogravimetric analysis (TGA: under nitrogen atmosphere, heating rate 10°C / min, 30°C to 300°C). The weight W of the reference film at 30°C O Weight of the reference film from (30℃) to 300℃ W O (300℃) is subtracted to obtain the weight loss of the reference film at 300℃ ΔW O The weight loss of the reference film was calculated. Since the reference film was produced by melt extrusion and then stretched, it did not contain any solvent. Therefore, the weight loss of the reference film, ΔW O was used as a reference in formula (X) described below.
[0140] In addition, the weight of the retardation film sample was measured by thermogravimetric analysis (TGA: under nitrogen atmosphere, heating rate 10°C / min, 30°C to 300°C) as described above. The weight W of the retardation film at 30°C R Weight of retardation film from (30℃) to 300℃ W R (300℃) to obtain the weight loss of the retardation film at 300℃ ΔW Rasked for.
[0141] The weight loss ΔW of the reference film at 300 °C O , and the weight loss ΔW of the retardation film at 300 ° C. R From the above, the solvent content of the retardation film was calculated by the following formula (X). Solvent content (%) = {(ΔW R -ΔW O ) / W R (30℃)}×100 (X)
[0142] [Production Example 1. Production of crystalline resin containing hydrogenated product of ring-opened polymer of dicyclopentadiene] A metallic pressure-resistant reactor was thoroughly dried and then purged with nitrogen. 154.5 parts of cyclohexane, 42.8 parts of a 70% cyclohexane solution of dicyclopentadiene (endo isomer content of 99% or more) (30 parts as dicyclopentadiene), and 1.9 parts of 1-hexene were added to the metallic pressure-resistant reactor and heated to 53°C.
[0143] 0.014 parts of tetrachlorotungsten phenylimide (tetrahydrofuran) complex was dissolved in 0.70 parts of toluene to prepare a solution. 0.061 parts of a 19% diethylaluminum ethoxide / n-hexane solution was added to this solution and stirred for 10 minutes to prepare a catalyst solution. This catalyst solution was added to a pressure-resistant reactor to start a ring-opening polymerization reaction. The reaction was then continued for 4 hours while maintaining the temperature at 53°C to obtain a solution of a ring-opened polymer of dicyclopentadiene. The number-average molecular weight (Mn) and weight-average molecular weight (Mw) of the obtained ring-opened polymer of dicyclopentadiene were 8,750 and 28,100, respectively, and the molecular weight distribution (Mw / Mn) calculated from these was 3.21.
[0144] To 200 parts of the obtained solution of the ring-opening polymer of dicyclopentadiene, 0.037 parts of 1,2-ethanediol was added as a terminator, heated to 60°C, and stirred for 1 hour to terminate the polymerization reaction. One part of a hydrotalcite-like compound (Kyowa Chemical Industry Co., Ltd.'s "Kyoward (registered trademark) 2000") was added, heated to 60°C, and stirred for 1 hour. Thereafter, 0.4 parts of a filter aid (Showa Chemical Industry Co., Ltd.'s "Radiolight (registered trademark) #1500") was added, and the adsorbent and the solution were filtered using a PP pleated cartridge filter (ADVANTEC Toyo Co., Ltd.'s "TCP-HX").
[0145] 100 parts of cyclohexane was added to 200 parts of the filtered ring-opening polymer solution (polymer amount 30 parts), and 0.0043 parts of chlorohydridocarbonyltris(triphenylphosphine)ruthenium was added, and hydrogenation reaction was carried out at 180°C and hydrogen pressure of 6 MPa for 4 hours. As a result, a reaction liquid containing a hydrogenated product of the ring-opening polymer of dicyclopentadiene was obtained. The reaction liquid was a slurry solution in which the hydrogenated product was precipitated.
[0146] The hydrogenated product and the solution contained in the reaction solution were separated using a centrifuge and dried under reduced pressure at 60°C for 24 hours to obtain 28.5 parts of a hydrogenated product of a crystalline ring-opening polymer of dicyclopentadiene. The hydrogenation rate of this hydrogenated product was 99% or more, the glass transition temperature (Tg) was 93°C, the melting point (Tm) was 262°C, and the ratio of racemo-dyads was 89%.
[0147] 100 parts of the obtained hydrogenated ring-opening polymer of dicyclopentadiene was mixed with 1.1 parts of an antioxidant (tetrakis [methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl) propionate] methane; "Irganox (registered trademark) 1010" manufactured by BASF Japan Ltd.), and then the mixture was put into a twin-screw extruder (product name "TEM-37B", manufactured by Toshiba Machine Co., Ltd.) equipped with four die holes having an inner diameter of 3 mm. The mixture of the hydrogenated ring-opening polymer of dicyclopentadiene and the antioxidant was molded into a strand shape by hot melt extrusion molding, and then chopped with a strand cutter to obtain a crystalline resin in the form of pellets. The operating conditions of the twin-screw extruder were as follows. Barrel temperature setting: 270~280℃ Die temperature setting = 250℃ Screw speed: 145 rpm
[0148] [Example 1] (1-1. Production of pre-stretched film) The pellet-shaped crystalline resin produced in Production Example 1 was molded using a hot melt extrusion film molding machine equipped with a T-die (Optical Control Systems' "Measuring Extruder Type Me-20 / 2800V3") and wound on a roll at a speed of 1.5 m / min to obtain a long unstretched film (thickness 50 μm) with a width of approximately 150 mm. The operating conditions of the film molding machine were as follows. Barrel temperature setting: 280℃~300℃ Die temperature = 270℃ Screw speed = 30 rpm Cast roll temperature = 80℃
[0149] (1-2. Production of oriented film) A stretching device ("SDR-562Z" manufactured by Etoh Corporation) was prepared. This stretching device was equipped with clips capable of holding the ends of a rectangular film and an oven, and was capable of biaxial stretching. A total of 24 clips were provided, five per side of the pre-stretched film and one at each vertex of the pre-stretched film, and the pre-stretched film could be stretched by moving these clips. In addition, two ovens were provided, and each could be set to a stretching temperature and a heat treatment temperature. Furthermore, in the stretching device, the film could be transferred from one oven to the other while still being held by the clips.
[0150] The pre-stretched film was cut into a rectangle of 130 mm length x 130 mm width. The retardation of the pre-stretched film obtained by cutting was measured using a phase difference meter ("AxoScan OPMF-1" manufactured by AXOMETRICS), and the in-plane retardation Re was 5 nm and the retardation in the thickness direction Rth was 6 nm. This pre-stretched film was attached to the stretching device and treated at a preheating temperature of 110°C for 10 seconds. Thereafter, the pre-stretched film was stretched at a stretching temperature of 110°C with a longitudinal stretching ratio of 1, a transverse stretching ratio of 1.5, and a stretching speed of 1.5 / 10 seconds. As a result, a stretched film was obtained as a film subjected to a stretching process.
[0151] The stretched film was removed from the stretching device and cooled to room temperature. FIG. 1 is a plan view showing the stretched film 10 obtained in Example 1. As shown in FIG. 1, the stretched film 10 was divided into three equal parts in the vertical direction and three equal parts in the horizontal direction, and nine measurement areas 11 to 19 of the same size and area were set. Then, in the center of each of the measurement areas 11 to 19, the retardation and birefringence were measured using a phase difference meter ("AxoScan OPMF-1" manufactured by AXOMETRICS). From the obtained measured values, the average in-plane retardation, the average thickness direction retardation, the average in-plane birefringence, and the average thickness direction birefringence of the stretched film 10 were calculated.
[0152] (1-3. Contact of stretched film with organic solvent) FIG. 2 is a plan view showing a jig 200 used in Example 1. As shown in FIG. 2, a jig 200 for fixing the stretched film 10 was prepared. The jig 200 had a frame material 220 provided in a rectangular shape so as to surround a space 210 for mounting the stretched film 10, a plurality of springs 230 attached to the frame material 220, and clips 240 provided at the tip of each spring 230. One end of each spring 230 was fixed to the frame material 220, and a clip 240 was provided at the other end. A total of 24 springs 230 and clips 240 were provided so that five positions per side of the rectangular stretched film 10 and each vertex of the stretched film 10 could be gripped by the clips 240. Furthermore, each spring 230 was provided so as to be able to apply tension to stretched film 10 by pulling it when clip 240 at the tip of spring 230 grips stretched film 10. With such jig 200, by adjusting the elongation of spring 230, a desired tension could be applied to stretched film 10 attached to space 210 surrounded by frame material 220.
[0153] The stretched film was cut into a rectangle of 120 mm length x 120 mm width. The stretched film 10 obtained by cutting was attached to a jig 200 as shown in FIG. 2. Specifically, the ends of the stretched film 10 (five points per side and each vertex, totaling 24 points) were held by clips 240. The elongation of the spring 230 was adjusted so that a tension of 40 N / m could be applied to the stretched film 10 in both the longitudinal and lateral directions. While being fixed to the jig 200 and tensioned in this manner, the stretched film 10 was immersed in a vat filled with toluene as an organic solvent for 60 seconds to obtain a retardation film.
[0154] (1-4. Drying) Thereafter, the retardation film was taken out of the toluene while still being fixed with the jig, and placed in an oven at 110° C. for 60 minutes to perform a drying treatment.
[0155] Thereafter, the retardation film was removed from the oven, cooled to room temperature, and then removed from the jig. The retardation film thus obtained was divided into three equal parts in the vertical direction and three equal parts in the horizontal direction, as in the case of the stretched film, to set nine measurement areas of the same size and area. Then, in the center of each measurement area, the retardation and birefringence were measured using (AXOMETRICS' "AxoScan OPMF-1"). From the obtained measured values, the average value and coefficient of variation of the in-plane retardation of the retardation film, the average value and coefficient of variation of the retardation in the thickness direction, the average value and coefficient of variation of the in-plane birefringence, the average value and coefficient of variation of the birefringence in the thickness direction, and the average value and coefficient of variation of the NZ coefficient were calculated. Furthermore, the thickness and the solvent content of the retardation film were measured by the above-mentioned methods.
[0156] [Example 2] In step (1-3), when the rectangular stretched film was attached to the jig, some clips were not used. Specifically, a pair of opposing sides (the right and left sides in FIG. 2) and each vertex of the stretched film were held by clips, and another pair of opposing sides (the lower and upper base sides in FIG. 2) of the stretched film were not held. Thus, in Example 2, the contact of the stretched film with the organic solvent and the drying of the obtained retardation film were carried out in a state where a tension of 40 N / m was applied in the lateral direction of the film. Except for the above, the retardation film was produced and evaluated in the same manner as in Example 1.
[0157] [Example 3] In the step (1-2), the transverse stretching ratio was changed to 2.5 times. Except for the above, the retardation film was produced and evaluated in the same manner as in Example 1.
[0158] [Example 4] In the step (1-2), the transverse stretching ratio was changed to 2.5 times. In addition, in the step (1-3), when the rectangular stretched film was attached to the jig, some clips were not used. Specifically, a pair of opposing sides (the right side and the left side in FIG. 2) and each vertex of the stretched film were held by clips, and another pair of opposing sides (the lower base side and the upper base side in FIG. 2) of the stretched film were not held. Thus, in Example 4, the contact of the stretched film with the organic solvent and the drying of the obtained retardation film were performed in a state where a tension of 40 N / m was applied in the lateral direction of the film. Except for the above, the retardation film was produced and evaluated in the same manner as in Example 1.
[0159] [Comparative Example 1] In steps (1-3) and (1-4), the stretched film and the retardation film were not attached to a jig. Specifically, in step (1-3), the stretched film was brought into contact with an organic solvent without anything attached thereto, and in step (1-4), the obtained retardation film was dried in a state of being attached to a flat plate with an adhesive tape. Except for the above, the retardation film was produced and evaluated in the same manner as in Example 1.
[0160] [Comparative Example 2] In the step (1-2), the transverse stretching ratio was changed to 2.5 times. In the steps (1-3) and (1-4), the stretched film and the retardation film were not attached to a jig. Specifically, in the step (1-3), the stretched film was brought into contact with the organic solvent without anything attached thereto, and in the step (1-4), the obtained retardation film was dried in a state of being attached to a flat plate. Except for the above, the retardation film was produced and evaluated in the same manner as in Example 1.
[0161] [Comparative Example 3] A stretched film was produced by the same method as steps (1-1) and (1-2) of Example 1. This stretched film was transferred to a heat treatment oven set at a heat treatment temperature of 170°C without removing it from the stretching device (Eto Corporation's "SDR-562Z"), while each side and each vertex of the film was held by clips. Then, heat treatment was performed in this oven for 20 seconds to obtain a retardation film. The obtained retardation film was cooled, and the average and coefficient of variation of in-plane retardation, the average and coefficient of variation of thickness retardation, the average and coefficient of variation of in-plane birefringence, the average and coefficient of variation of thickness birefringence, the average and coefficient of variation of NZ coefficient, thickness, and solvent content were measured by the same method as in Example 1.
[0162] [Comparative Example 4] The stretching ratio in producing the stretched film was changed to 2.5 times. Except for the above, the retardation film was produced and evaluated in the same manner as in Comparative Example 3.
[0163] [result] The results of the examples and comparative examples are shown in the table below. In comparative examples 3 and 4, the stretched films obtained by the stretching process were subjected to heat treatment without being removed from the stretching device. Therefore, the optical properties of the stretched films in comparative examples 3 and 4 could not be measured. Therefore, in the column for the stretched films in comparative examples 3 and 4 in the table below, the properties of stretched films separately produced by the same method as comparative examples 3 and 4 are listed.
[0164] In the table below, the meanings of the abbreviations are as follows: Re: In-plane retardation. Rth: Retardation in the thickness direction CV(Re): Coefficient of variation of in-plane retardation. CV(Rth): Coefficient of variation of retardation in the thickness direction. Δn (in-plane direction): Birefringence in the in-plane direction. Δn (thickness direction): Birefringence in the thickness direction.
[0165] [Table 1] [Explanation of symbols]
[0166] 10 Stretched film 11~19 Measurement area 200 Jig 210 Space for attaching stretch film 220 Frame material 230 Spring 240 clips
Claims
[Claim 1] A method for producing a retardation film formed of a resin containing a crystalline polymer, comprising the steps of: A first step of preparing a stretched film formed from the resin; a second step of contacting the stretched film with an organic solvent; In the second step, tension is applied to the stretched film, The retardation film has an in-plane retardation coefficient of variation CV (Re) of 1.0% or less at a measurement wavelength of 590 nm; The average value of the NZ coefficient of the retardation film is greater than 0.0 and less than 1.0; The retardation film contains the organic solvent in an amount of 0.01 ppm or more and 10% by weight or less relative to 100% by weight of the retardation film, the crystalline polymer is a hydrogenated ring-opening polymer of dicyclopentadiene, The method for producing a retardation film, wherein the coefficient of variation CV(Re) is calculated by dividing the standard deviation of the in-plane retardation Re of the retardation film by the average value of the in-plane retardation Re, and converting the result into a percentage.
Citation Information
Patent Citations
Electric lock control system
JP1989006479A
Molded styrene-based polymer product and production thereof
JP1990064141A
Phase difference plate, circularly polarizing plate and reflection type liquid crystal display device which uses the same
JP2002131538A
Hydrogenated product of alicyclic structure-containing ring-opened polymer and its use
JP2014091793A
Method for producing resin film, resin film, and optical film
JP2016026909A